EPISTEMOLOGICAL FOUNDATIONS OF ISLAMIC EDUCATION CURRICULUM IN THE HADITH OF AT-TIRMIDHI AND AD-DARIMI - Almuzakky, Alamul Huda (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2026)
The curriculum is a number of subjects taken by students in an educational institution, and in a broad sense the curriculum is "what persons experience in a setting" all the experiences and learning culture created by an educational institution to build independence and achieve the desired educational goals. While the Islamic education curriculum is an educational curriculum that has a foundation based on Islam, namely the Qur'an and Hadith, which pays close attention to the condition of human personality or students such as physical aspects, intellectual aspects and spiritual aspects. Hadith as the second source of law after the Qur'an is the foundation in compiling the Islamic education curriculum. However, we will not find a special word in the Hadith such as manhaj al-dirasah as a word that indicates the curriculum. So the curriculum in the study of the Tarbawi Hadith is a stretch of values, culture, character, principles, teachings that are spread out in the treasure of hadith, which is an example of the application of the Qur'an by the Prophet Muhammad SAW.